2008
DOI: 10.1063/1.2940591
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly low thermal conductivity in natural nanostructured bulk Ga2Te3

Abstract: Here we introduce a promising thermoelectric material: Ga2Te3 with unexpectedly low thermal conductivity, in which certain kinds of superlattice structures naturally form. Two-dimensional vacancy planes with approximately 3.5nm intervals exist in Ga2Te3, scattering phonons efficiently and leading to a very low thermal conductivity, comparable to its calculated minimum. Ga2Te3 and related materials hold great promise in the field of thermoelectrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 14 publications
3
77
0
Order By: Relevance
“…[110] direction. [151] Reprint with permission from AIP Publishing LLC. Ag nanoparticles [47a] No resonant doping, K induced lattice expansion caused distortion of DOS, doping effect …”
Section: Discussionmentioning
confidence: 99%
“…[110] direction. [151] Reprint with permission from AIP Publishing LLC. Ag nanoparticles [47a] No resonant doping, K induced lattice expansion caused distortion of DOS, doping effect …”
Section: Discussionmentioning
confidence: 99%
“…Desai et al demonstrated that In 2 Te 3 has two components, a low-temperature a-phase with regularly ordered vacancies and a high-temperature b-phase with fully disordered vacancies; the former transforms to the latter at about 893 K. 11 a-In 2 Te 3 has a facecentered cubic lattice with a = 1.850 nm, which is approximately three times the lattice parameter of b-In 2 Te 3 (a = 0.616 nm). On the other hand, it has been observed that Ga 2 Te 3 has a mesoscopic superstructured phase, having periodic vacancy planes, 12,13 as observed in Ga 2 Se 3 . 14 We hypothesized that, if we could create such vacancy planes in the bulk samples and control their size and periodicity, we could achieve a low j, due to the effective phonon scattering by the vacancy planes.…”
Section: Introductionmentioning
confidence: 94%
“…The effect of the amount of vacancies on the TE properties of the CuGaTe ternary compounds with zinc-blende or chalcopyrite structure was examined on the polycrystalline samples of Cu 3 than that of the ¬ lat . These results imply that the presence of vacancies degrades the TE performance of the CuGaTe ternary compounds; in other words, CuGaTe 2 containing no vacancies will show the best TE figure of merit.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of the amount of vacancies on the TE properties has not been investigated. In the CuGaTe ternary system, there exist various compounds with zinc-blende or chalcopyrite structure containing vacancies, viz., Cu 3 In the present study, we tried to clarify the effect of the amount of vacancies on the TE properties of the CuGaTe ternary compounds. Especially, the relationships between the amount of vacancies and the ¬ lat or the Hall mobility (® H ) were investigated.…”
Section: Introductionmentioning
confidence: 99%